Analisis Stabilitas Lereng Dengan Variasi Lapisan Tanah Berbeda Yang Di Pengaruhi Nilai Kohesi Tanah - Atmoko, Fajar Destri; Afriani, Lusmeilia; Zakaria, Ahmad (Universitas Lampung, 2020)
Natural disasters often occur in hilly areas in Lampung Province, namely landslides. Slides thatoccur due to increased soil pore water pressure. The GeoStudio SLOPE / W 2012 program cananalyze slope stability which can be modeled according to the original conditions in the field andcan determine the value of the slope safety factor. In this study, there are four cross sections ofslopes with four different layers with an angle of 30 ° each, and following a maximum height of 18meters.The results of the analysis of the GeoStudio Slope / W 2012 program using 4 methods of analysis,namely Ordinary, Bishop, Janbu and Morgenstern Price, obtained different safe factor values, theMorgenstern Price method and the Bishop method have a safe factor value that tends to be thesame and greater than the Ordinary method and the method. Janbu tends to have a smaller safetyfactor.The shape of the cross section of the slope in the 5 soil layers is the most safe factor, different soillayers, it can be seen that each layer of soil has different safety factors but does not differ muchfrom the others.